Risk Management Status of Waste Anesthetic Gases Using ECRI Institute Standards - S Asefzadeh; AR Raeisi; A Mousavi (Tehran University of Medical Sciences, 2012)
Background: The aim of this study was assessment the risk management status of waste anesthetic gases in academicals hospitals in Iran to prevent from harmful effects of these gases on employees' health.Methods: A descriptive-analytic study was designed in 2011. Standard structured checklist developed by ECRI institute (Emergency Care Research Institute) was applied. Checklists were filled onsite through direct observation and interviews with anesthesia personnel in 46 operating rooms at 4 hospitals from all of the hospitals under affiliation of Isfahan University of Medical Sciences. These hospitals were selected based on the number of surgical beds.Results: Total means score of WAGs risk management status was 1.72 from the scale of 3. In the studied operating rooms, only 28% complied with predetermined standards, 16% needed improvement and 56% had no compliance. Total mean scores of compliance in planning, training and evaluation and monitoring of waste anesthetic gases were weak and equipment and work activity was at medium level.Conclusion: The risk management status of waste anesthetic gases in the hospitals to be weak, therefore operating room personnel are exposed to medium to high level of these gases. The hospital mangers should prepare and apply scavenging equipment, development of control program, quality improvement, risk management and maintenance of anesthesia equipment. Finally, ongoing monitoring and evaluation, education to personnel and modification of policy and procedures and improvement of work activities should be considered.